GESTÃO DE SERVIÇOS: DIAGNÓSTICO E ANALISE EM ORGANIZAÇÕES E SETORES NA REGIÃO FRONTEIRA NOROESTE DO ESTADO DO RS - Büttenbender, Pedro L.; Sparemberger, Ariosto; Zamberlan, Luciano; Scolari, Ana G. X.; Oliveira, Gustavo d.; Loose, Roberta F. (Salão do Conhecimento, 2013)
Resumo